A thermo-elastoplastic self-consistent homogenization method for inter-granular plasticity with application to thermal ratcheting of TATB - Kane C. Bennett (Advanced Modeling and Simulation in Engineering Sciences, 2020)
Abstract A novel thermo-elastoplastic self-consistent homogenization model for granular materials that exhibit inter-granular plasticity is presented. The model, TEPSCA, is made possible by identifying a new inter-granular plastic Eshelby-like tensor. A micromechanical model of interfacial yielding between grains of a Mohr–Coulomb type is provided, which is relatable to the description of imperfect interfaces within the paradigm of self-consistent homogenization. The local grain constitutive laws are consistent with the description of an interphase layer comprised of local pore volume between grains, such that inelastic inter-particle displacements are directly relatable to changes in bulk porosity, i.e., dilation. The model was developed for the purpose of modeling thermally induced plasticity—the phenomenon known as thermal ratcheting or “ratchet growth”—of composites made from the high explosive triaminotrinitrobenzene (TATB). Model simulations are compared to ratchet growth measurements during cyclic thermal loading of a TATB pellet under stress-free conditions.